2011
DOI: 10.1088/0022-3727/44/45/455308
|View full text |Cite
|
Sign up to set email alerts
|

Red, green, blue and white light upconversion emission in Yb3+/Tm3+/Ho3+ co-doped tellurite glasses

Abstract: Several Yb3+/Tm3+/Ho3+ co-doped transparent TeO2–ZnO–Na2O–Yb2O3–Ho2O3–Tm2O3 glasses were prepared and luminescence properties were characterized. Simultaneous red, green and blue (RGB) emission were obtained after excitation at 970 nm. Colour emission was tuned from multicolour to white light with colour coordinate (0.32, 0.33) matching very well with the white reference (0.33, 0.33). Changes in colour emission were obtained by varying the intensity ratios between RGB bands that are strongly concentration depe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 25 publications
0
19
0
1
Order By: Relevance
“…YVO 4 :Yb,Er powders in KBr pellets were excited at 975 nm using a 1 W laser diode (L975P1WJ Thorlabs) and their UC emission was detected with an Ocean Optics spectrometer (QE 65 000). To compare the efficiency of the different samples, green and red emissions were integrated between 500 and 600 nm and 600 and 700 nm, respectively, and normalized in acquisition time.…”
Section: Methodsmentioning
confidence: 99%
“…YVO 4 :Yb,Er powders in KBr pellets were excited at 975 nm using a 1 W laser diode (L975P1WJ Thorlabs) and their UC emission was detected with an Ocean Optics spectrometer (QE 65 000). To compare the efficiency of the different samples, green and red emissions were integrated between 500 and 600 nm and 600 and 700 nm, respectively, and normalized in acquisition time.…”
Section: Methodsmentioning
confidence: 99%
“…For example, in the case of UC process, Yb 3+ is a well-known sensitizer ion for Er 3+ , Ho 3+ , Tm 3+ , and Pr 3+ , which makes it possible to obtain strong emissions while in its absence it is impossible [4,[14][15][16]. In addition, it has been reported that the use of Li 2+ and Gd 3+ enhances the visible emission from Eu 3+ and Er 3+ , respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Sources of white light has been wide studied since it find applications in many fields, such as three dimensional displays, long lifetime, low-energy light sources, back light and so on [1][2][3][4][5][6][7][8][9][10][11]. One of the effective ways of generating white light is the upconversion in which near-infrared excitation is converted into a visible emission through lanthanide doping.…”
Section: Introductionmentioning
confidence: 99%
“…The excitation source of upconversion is an infrared laser, which is compact, power-rich, inexpensive, and can be commercially available. Up to now, there have been several reports on upconversion white luminescence from Tm 3+ /Er 3+ /Yb 3+ or Tm 3+ /Ho 3+ /Yb 3+ doped glasses/powders/ceramic/nanocrystals, such as tellurite glasses [9,10], Y 2 O 3 nanocrystals [11], Y 2 O 3 transparent ceramic [12], Lu 2 O 3 nanocrystals [13], GdVO 4 nanocrystals [14], KY 3 F 10 nanocrystals [4], CaSnO 3 powders [15], Gd 4 O 3 F 6 nanocrystals [16], NaYF 4 nanorods [17] and fluoride glasses [18,19]. For example, Zhang's group studied color control and white light generation of upconversion luminescence by operating dopant concentrations and pump densities in Tm 3+ /Er 3+ /Yb 3+ tri-doped Lu 2 O 3 nanocrystals [13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation